2019
DOI: 10.1590/2358-2936e2019009
|View full text |Cite
|
Sign up to set email alerts
|

Grooming behaviors and fouling of the spider crab Libinia dubia (Decapoda: Epialtidae)

Abstract: Body fouling has been reduced by grooming behaviors. In decapods, grooming has been focused on gills, sensory structures, and jointed appendages. In this study, grooming behaviors of the spider crab, Libinia dubia H. Milne-Edwards, 1834, were examined; this brachyuran crab decorates and camouflages body regions by attaching materials onto hooked setae. The relationship between grooming and these camouflaged body regions was unknown. Six observational and experimental studies examined the grooming frequency, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…All setal types observed in this study are described in Libinia and in body regions decorated in spider crabs (Berke & Woodin, 2009; Hultgren & Stachowicz, 2011; Szebeni & Hartnoll, 2005; Wortham & Jedlicka, 2019). While Szebeni and Hartnoll (2005) estimated 2.6 setal types per species of spider crabs, the spider crabs in this study have more setal types (8) than this previously reported average.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…All setal types observed in this study are described in Libinia and in body regions decorated in spider crabs (Berke & Woodin, 2009; Hultgren & Stachowicz, 2011; Szebeni & Hartnoll, 2005; Wortham & Jedlicka, 2019). While Szebeni and Hartnoll (2005) estimated 2.6 setal types per species of spider crabs, the spider crabs in this study have more setal types (8) than this previously reported average.…”
Section: Discussionmentioning
confidence: 76%
“…While research has suggested that larger individuals do not decorate due to the lack of predation (Guinot & Wicksten, 2015; Hultgren & Stachowicz, 2009), Libinia individuals are smaller than the carapace widths reported in these previous studies (CW >10 cm). Wortham and Jedlicka (2019) also reported that in Tampa Bay, predators exist that feed on spider crabs (Springer & Woodburn, 1960). A lack of hooked setae may be driving decreases in decorating behaviors, while not decreasing the ability to camouflage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations